A redox active switch for lanthanide luminescence in phenolate complexes. Issue 3 (16th December 2016) - Molloy, J. K.; Jarjayes, O.; Philouze, C.; Fedele, L.; Imbert, D.; Thomas, F.
Abstract : The reversible oxidation of coordinated phenolates into phenoxyl radicals results in a dramatic quenching (>95%) of the luminescence of the f metal ion. Abstract : The reversible oxidation of coordinated phenolates into phenoxyl radicals results in a dramatic quenching (>95%) of the luminescence of the f metal ion.